Utility of Soluble CD163 in the Clinical Management of Patients With Kawasaki Disease - Azuma, Yoshihiro; Suzuki, Yasuo; Okada, Seigo; Matsuguma, Chie; Wakiguchi, Hiroyuki; Ohnishi, Yuji; Furuta, Takashi; Miyake, Akiko; Yasudo, Hiroki; Ichihara, Kiyoshi; Ohga, Shouichi; Hasegawa, Shunji (Frontiers in Pediatrics, 2020)
Objective: Intravenous immunoglobulin (IVIG) therapy is a useful first-line treatment for Kawasaki disease (KD); however, 10–20% of patients fail to respond and require additional IVIG. Soluble CD163 (sCD163) is considered a biomarker for macrophage activation. There are no reports measuring serum sCD163 in KD patients. This study aimed to explore its possible utility in the clinical management of patients with KD. Methods: Eighty-seven patients with well-defined KD were retrospectively enrolled together with 19 healthy individuals with comparable ages. KD patients were classified into three groups, Group A (initial IVIG responders), Group B (additional IVIG responders), and Group C (additional IVIG non-responders). Serum sCD163 together with complete blood counts, C-reactive protein, d-dimer, albumin, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) were measured before the initial IVIG treatment in all cases, and afterward in a fraction of cases. Results: Serum sCD163 in KD patients before initial IVIG was generally much higher than the control group. The median (interquartile range) of sCD163 was as follows: Control 446 (385–521) ng/mL; Group A, 699 (478–1,072); Group B, 1,349 (1,116–1,390); and Group C, 665 (544–1,094). In general, sCD163 showed close positive correlation with ALT and AST, but none with other markers. Among the KD groups, Group B showed the highest sCD163: Group B vs. A: p = 0.0003; B vs. C: p = 0.035). Serum sCD163 was significantly increased after IVIG in Group A, while no change occurred in others. Conclusion: The serum sCD163 levels could be a useful biomarker in the clinical management of KD, especially for predicting responsiveness to IVIG.